2021
DOI: 10.1021/acs.jafc.1c00499
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Quantitative Analysis of Goat Milk Oligosaccharides: Composition, Variation, Associations, and 2′-FL Variability

Abstract: Human milk oligosaccharides (hMOS) are associated with health benefits for newborns. We studied the composition of goat MOS (gMOS) from colostrum up to the 9th month of lactation to conceive an overview of the structures present and their fate. Potential correlations with factors such as age, parity, and lifetime milk production were examined. An effective method for gMOS extraction and ultra-high-performance liquid chromatography coupled to fluorescence detection (UPLC-FLD) analysis was established, following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…All the gMOS characterized in this study have been found in caprine milk and colostrum in previous studies ( Albrecht et al, 2014 ; Chatziioannou et al, 2021 ; Lu et al, 2020 ; Urashima et al, 1994 ; Urashima et al, 1997 ; van Leeuwen et al, 2020 ). This is to confirm that different proportions of SOS ( Claps et al, 2014 ; Claps et al, 2016 ), share a common profile of neutral and acidic/SOS as they belong to the same species of Capra hircus .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…All the gMOS characterized in this study have been found in caprine milk and colostrum in previous studies ( Albrecht et al, 2014 ; Chatziioannou et al, 2021 ; Lu et al, 2020 ; Urashima et al, 1994 ; Urashima et al, 1997 ; van Leeuwen et al, 2020 ). This is to confirm that different proportions of SOS ( Claps et al, 2014 ; Claps et al, 2016 ), share a common profile of neutral and acidic/SOS as they belong to the same species of Capra hircus .…”
Section: Discussionsupporting
confidence: 65%
“…Heterogeneity of oligosaccharides was observed among animals. Several studies have been done to characterize MOS from colostrum and milk of dairy animals such as: cows ( Albrecht et al, 2014 ; Barile et al, 2010 ; Nakamura et al, 2003 ; Saito et al., 1984 ; Saito et al, 1987 ), goats ( Albrecht et al, 2014 ; Chatziioannou et al, 2021 ; Claps et al, 2014 ; Claps et al, 2016 ; Lu et al, 2020 ; Martín-Ortiz et al, 2016 ; Martín-Ortiz et al, 2017 ; Martinez-Ferez et al, 2006a ; Martinez-Ferez et al, 2006b ; Urashima et al, 1994 ; Urashima et al, 1997 ; Viverge et al, 1997 ), sheeps ( Nakamura et al, 1998 ; Sasaki et al, 2016 ), camels ( Alhaj et al, 2013 ; Fukuda et al, 2010 ), and reindeer ( Taufik et al, 2014 ). MOS content is varied in the milk or colostrum of different dairy species.…”
Section: Introductionmentioning
confidence: 99%
“…All milk samples were collected 14 days postpartum. Due to the determination results may be influenced by factors such as individual genotype and age/livestock age. , Therefore, the milk samples of four species were mixed by equal volume, respectively, to reduce inter-individual differences, and the four different milk types were mixed in equal proportions and quantified three times ( n = 5). All samples were stored at −80 °C.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Over the years, 169 structures of h MOS have been structurally characterized, , compared to up to 40 for b MOS and about 55 for g MOS. The difference in the identified structures can partially be explained by the fact that human milk is studied more intensely than other milk types with multiple techniques, leading to a higher number of identified oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%